ChemInform Abstract: Pressure‐Induced Transformations in PrVO4 and SmVO4 and Isolation of High‐Pressure Metastable Phases. Issue 28 (21st June 2013) - Errandonea, Daniel; Achary, S. Nagabhusan; Pellicer‐Porres, Julio; Tyagi, Avesh K.
Abstract High‐pressure phases of PrVO4 and SmVO4 are synthesized from the zircon‐structured compounds at 12 GPa and room temperature (24 h).